2017
DOI: 10.1371/journal.pone.0179957
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel fungus, Trichoderma asperellum GDFS1009, and comprehensive evaluation of its biocontrol efficacy

Abstract: Due to its efficient broad-spectrum antimicrobial activity, Trichoderma has been established as an internationally recognized biocontrol fungus. In this study, we found and identified a novel strain of Trichoderma asperellum, named GDFS1009. The mycelium of T. asperellum GDFS1009 exhibits a high growth rate, high sporulation capacity, and strong inhibitory effects against pathogens that cause cucumber fusarium wilt and corn stalk rot. T. asperellum GDFS1009 secretes chitinase, glucanase, and protease, which ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
87
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 56 publications
4
87
2
5
Order By: Relevance
“…Out of them, isolates showed strong antagonistic activity inhibiting over 50% mycelia growth of F. oxysporum, R.s olani and B. cinerea. Wu et al (2017) [41] reported an inhibition rate of 80.82% of new Trichoderma asperellum isolate against F. oxysporum, an aggressive pathogen infecting cucumber plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of them, isolates showed strong antagonistic activity inhibiting over 50% mycelia growth of F. oxysporum, R.s olani and B. cinerea. Wu et al (2017) [41] reported an inhibition rate of 80.82% of new Trichoderma asperellum isolate against F. oxysporum, an aggressive pathogen infecting cucumber plants.…”
Section: Discussionmentioning
confidence: 99%
“…The secreted enzymes act synergistic each other, but at the same time with other metabolites. It has been reported that characteristics of chitinases are different at Trichoderma species [41].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Trichoderma isolates on tomato plant growth parameters. J2), number of galls, egg masses and females per root system with 90.33, 90.59, 90.06 and 85.50%, respectively and the effect of this isolate was similar to vydate Wu et al (2017). isolated new strain of T. asperellum with high antagonism against pathogens of cucumber wilt and corn stalk rot.…”
mentioning
confidence: 61%
“…These results confirm the efficiency of barcode DNA and are compatible with previous studies that employed ITS to identify Trichoderma spp. (Wu et al, 2017;Fahmi et al, 2016;Savitha and Sriram, 2015;Oskiera et al, 2015).…”
Section: Isolation and Molecular Identification Of Trichoderma Isolatesmentioning
confidence: 99%
“…Отмеченное в нашем исследовании увеличение биометрических показателей растений картофеля и рост урожайности, а также повышение эффек-тивности традиционной интегрированной защиты картофеля открывают перспективу разработки биопрепаратов защитного назначения, сочетающих в себе также свойства биоудобрений и биостимуляторов (39)(40)(41)(42)(43). Применение экспериментальных образцов полифункциональных биопрепаратов на основе T. asperellum Т-36 и B. subtilis B-10 в полевых условиях в принятых нормах расхода обеспечило достоверный защитный эффект, соответствующий описанному в мировых разработках у аналогичных препаратов (44)(45)(46)(47).…”
Section: эффективность лабораторных образцов новых мультиконверсионныunclassified